ABMA, a small molecule that inhibits intracellular toxins and pathogens by interfering with late endosomal compartments. Issue 1 (December 2017) - Wu, Yu; Pons, Valérie; Goudet, Amélie; Panigai, Laetitia; Fischer, Annette; Herweg, Jo-Ana; Kali, Sabrina; Davey, Robert; Laporte, Jérôme; Bouclier, Céline; Yousfi, Rahima; Aubenque, Céline; et al.
Abstract Intracellular pathogenic microorganisms and toxins exploit host cell mechanisms to enter, exert their deleterious effects as well as hijack host nutrition for their development. A potential approach to treat multiple pathogen infections and that should not induce drug resistance is the use of small molecules that target host components. We identified the compound 1-adamantyl (5-bromo-2-methoxybenzyl) amine (ABMA) from a cell-based high throughput screening for its capacity to protect human cells and mice against ricin toxin without toxicity. This compound efficiently protects cells against various toxins and pathogens including viruses, intracellular bacteria and parasite. ABMA provokes Rab7-positive late endosomal compartment accumulation in mammalian cells without affecting other organelles (early endosomes, lysosomes, the Golgi apparatus, the endoplasmic reticulum or the nucleus). As the mechanism of action of ABMA is restricted to host-endosomal compartments, it reduces cell infection by pathogens that depend on this pathway to invade cells. ABMA may represent a novel class of broad-spectrum compounds with therapeutic potential against diverse severe infectious diseases.